2007
DOI: 10.1002/ijc.22533
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromosome 10 aberrations in rat endometrial cancer—evidence for a tumor suppressor locus distal to Tp53

Abstract: We have recently shown in the BDII rat model of human endometrial adenocarcinoma (EAC), rat chromosome 10 (RNO10) is frequently involved in chromosomal aberrations. In the present study, we investigated the association between RNO10 deletions, allelic imbalance (AI) at RNO10q24 and Tp53 mutation in 27 rat EAC tumors. We detected chromosomal breakage accompanied by loss of proximal and/or gain of distal parts of RNO10 in approximately 2/3 of the tumors. This finding is suggestive of a tumor suppressor activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…In type I tumors, abnormalities of Tp53 are suggested as late events and are thought to be important step in the progression to high-grade tumors (Ryan et al 2005). Earlier, we found recurrent Tp53 mutations (67%) in BDII rat EAC tumors (Nordlander et al 2007). However, in majority of the mutations resulting in amino acid exchange, the hydrophobicity or hydrophilicity was maintained by equivalent substitutions.…”
Section: E Samuelson Et Al: Molecular Classification Of Bdii Rat Eacmentioning
confidence: 55%
See 4 more Smart Citations
“…In type I tumors, abnormalities of Tp53 are suggested as late events and are thought to be important step in the progression to high-grade tumors (Ryan et al 2005). Earlier, we found recurrent Tp53 mutations (67%) in BDII rat EAC tumors (Nordlander et al 2007). However, in majority of the mutations resulting in amino acid exchange, the hydrophobicity or hydrophilicity was maintained by equivalent substitutions.…”
Section: E Samuelson Et Al: Molecular Classification Of Bdii Rat Eacmentioning
confidence: 55%
“…Frequent Tp53 mutations (Nordlander et al 2007) and lack of K-ras mutation were shown in BDII rat EACs. Additionally, neither microsatellite instability (Behboudi et al 2001, Adamovic et al 2005, Nordlander et al 2005 nor Erbb2 amplifications were previously found among BDII rat tumors.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations